KAWIN MASSAL/MAKANDAL MASSAL STUDI KASUS DI DESA SONGAN A DAN B KECAMATAN KINTAMANI, KABUPATEN BANGLI - Gede Rai Parsua; I Gusti Ngurah Triyana (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
The most common marriage in Bali is the marriage of marriage (asking) by the man to the woman's house. The cost of a marriage in this modern era is quite large due to several stages such as mesedek (telling women), proposing marriage (taking) and marriage ceremony to reception. Some things that cause the mass wedding ceremony in Songan are eloping, taking more than one electricity, where the second, third and so on wives are celebrated with mass marriage. Besides that, there are also couples who have not graduated from school to get married, they die, and economic partners are weak. Before the mass wedding ceremony is held in the Village Temple, the beakaon stages are first performed at their respective homes. The stages of metipatbantalan (coming to a woman's house) for the deceased are usually carried out after being disbursed by mepiuning / Nangiang Dewa Hyang to be invited to be invited to the house of women with the symbol of the dagger or Daksina as befits a person who is still living with the same process. The research problem formulation is (1) What are the Forms of Mass Marriage in Songan, Kintamani, Bangli Villages? (2) Why Mass Marriage is conducted in Songan, Kintamani, Bangli? ? Theories used are structural functionalist theory, phenomenology theory and social change theory. The research method used is a qualitative method. Mass marriages and non-mass marriages in Songan conducted at Bale Agung Temple are declared valid if it has been witnessed by Tri Upasaksi (three witnesses) namely Bhuta Witness, Manusa Witness, Dewa Witness. Implications of a Mass Marriage for a couple who have been legally married in Songan have an impact on the obligation to pay or pay for marriage to pay offspring or ceremonial and grief costs to the Adat Village.